Homosexuality : opposing viewpoints - Dudley, William, 1964- (San Diego, CA : Greenhaven Press, 1993)
Presents opposing viewpoints on such aspects of homosexuality as what causes it, how society should treat homosexuals, and whether sexual orientation can be changed.
What causes homosexuality? -- Should society encourage increased acceptance of homosexuality? -- Can homosexuals change their sexual orientation? -- Should society legally sanction gay relationships?
Includes bibliographical references and index.
Keywords: Homosexuality -- United States; Gays -- United States